التقنيات التي يعتمدها مشروع الفلاحة الايكولوجية ( Working sheet for farmers to fill in (AE technologies) - Rudiger, Udo; Ouerghemmi, Hassen (2023)
Farmers were supposed to look at the pictures of different AE technologies and select important ones.